2017
DOI: 10.1080/15412555.2017.1320370
|View full text |Cite
|
Sign up to set email alerts
|

Variants of the ADRB2 Gene in COPD: Systematic Review and Meta-Analyses of Disease Risk and Treatment Response

Abstract: The β-adrenergic receptor (ADRB) is an important regulator of airway smooth muscle tone in chronic obstructive pulmonary disease (COPD). Variants that impair ADRB function could increase disease risk or reduce the response to endogenous and inhaled adrenergic agonists in COPD. We performed a systematic review and three meta-analyses to assess whether three functional variants (Thr164Ile, Arg16Gly, and Gln27Glu) in the ADRB gene are associated with elevated risk of disease or reduced therapeutic response to inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…The microarray analysis employed in the current study revealed that ADRB2 and HSP90AA1 are downregulated in SCC tissues compared with healthy adjacent non-cancerous tissue, suggesting that they may serve important roles in the progression of SCC. Previous studies reported that ADRB2 is an important regulator of airway smooth muscle tone (14)(15)(16). High levels of ADRB2 are associated with reduced lung function, asthma and COPD (14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The microarray analysis employed in the current study revealed that ADRB2 and HSP90AA1 are downregulated in SCC tissues compared with healthy adjacent non-cancerous tissue, suggesting that they may serve important roles in the progression of SCC. Previous studies reported that ADRB2 is an important regulator of airway smooth muscle tone (14)(15)(16). High levels of ADRB2 are associated with reduced lung function, asthma and COPD (14).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that ADRB2 is an important regulator of airway smooth muscle tone (14)(15)(16). High levels of ADRB2 are associated with reduced lung function, asthma and COPD (14). Additionally, ADRB2 is an anti-inflammatory gene and was previously reported to be involved in hyperinflammation (17) and autoimmune disorders such as rheumatoid arthritis (18).…”
Section: Discussionmentioning
confidence: 99%
“…Systematic reviews of COPD prevalence have been limited to risk factors [6][7][8][9][10][11][12] , clinical complications [13][14][15] , comorbidities 16 , economic impact [17][18][19] , and treatment of the disease [20][21][22] . However, the scientific evidence about the occurrence of COPD in populations in developing countries, like Brazil, is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies do not allow drawing an unequivocal conclusion about the involvement of ADRB2 polymorphisms in predisposition of COPD and response of COPD patients to treatment with beta‐2‐agonists. Meta‐analyses included 85 381 studies’ participants and did not find a significant association of Arg16Gly and Gln27Glu polymorphisms with the risk of disease and therapeutic effects of inhaled beta‐2‐agonists. Hussein et al revealed an association of the Arg16 genotypes with highly pronounced respiratory symptoms and frequent exacerbations in Egyptian patients with COPD, and these findings were consistent with our data.…”
Section: Discussionmentioning
confidence: 99%